Website-Based Budget Adjustment Information System at PT. Taspen (Persero) Denpasar Branch Office - Mahmuda Lailiya; Ni Luh Wiwik Sri Rahayu Ginantra; Gede Surya Mahendra (Yayasan Literasi Sains Indonesia, 2022)
The activities of the budget adjustments in the manufacture of the allocation of procurement of goods still have not been done optimally. This leads to lack of control over spending budget. The purpose of this research is to make the Information Systems Budget Adjustments Purchase Website Based on PT. Taspen (Persero) Kantor Cabang Denpasar, which is the solution of the weakness of the existing system. This study aims to produce a system that will simplify and accelerate the employees of PT. Taspen (Persero) Denpasar in adjusting the budget the purchase of equipment and supplies so as to produce the management of the orderly, effective, and efficient. The stages in achieving this goal based on the methods of the waterfall includes Flowmap, Context Diagram, Data Flow Diagram, Entity Relationship Diagram, and database design using software package xampp and MySQL. Testing methods carried out using black box testing. The results obtained in the form of the establishment of a system that supports the process of inputting the data of the budget, the calculation of the adjustment of the budget, and reporting the data required as an accountability report